Thermal barrier coating material and method of making and using same, hot section component

CN122979805APending Publication Date: 2026-10-27TSINGHUA UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611389073.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

(1)低热导率:低热导率可显著降低高温燃气向内部结构件基体的热量传递,给热端结构件提供更优异的隔热防护效果,有效减少冷却气用量,提升动力装备的整体热效率与推重比。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979805A_ABST
    Figure CN122979805A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of protective coating, in particular to a thermal barrier coating material and a preparation method and application thereof, and a hot end structural member. x M (1‑x) O (2‑x / 2) , wherein Re comprises at least two of Sm, Gd, Dy, Y, Er, Yb and Lu, M comprises Hf and at least one of Zr and Ce, and x is 0.2-0.4. The thermal barrier coating material has low thermal conductivity, a high expansion coefficient and excellent sintering resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of protective coating technology, and in particular to thermal barrier coating materials, their preparation methods and applications, and hot-end structural components. Background Technology

[0002] As the operating temperatures of hot-end structural components in high-temperature gas turbines and aero engines increase (exceeding 1300℃), higher demands are placed on thermal protection coatings. Compared to traditional YSZ (yttrium-stabilized zirconium oxide) coatings, new coating materials need to possess lower thermal conductivity and superior resistance to sintering. After extensive research, rare-earth zirconates are considered candidates for next-generation advanced thermal barrier coating materials due to their excellent phase stability and low thermal conductivity.

[0003] However, related technologies have revealed that rare earth zirconates (such as La2Zr2O7) still have shortcomings: single rare earth zirconates have high thermal conductivity and relatively poor resistance to sintering, while also needing to ensure a higher coefficient of thermal expansion, which limits their engineering application under long-life conditions above 1300℃.

[0004] Therefore, there is an urgent need to develop a thermal barrier coating material that can solve the above problems. Summary of the Invention

[0005] This application aims to at least partially address one of the technical problems in related technologies. To this end, this application proposes thermal barrier coating materials, their preparation methods and applications, and hot-end structural components. This application provides a thermal barrier coating material with low thermal conductivity, a high coefficient of thermal expansion, and excellent resistance to sintering.

[0006] A first aspect of this application provides a thermal barrier coating material, the chemical formula of which is: Re x M (1-x) O (2-x / 2) In the formula: Re includes at least two of Sm, Gd, Dy, Y, Er, Yb and Lu, M includes Hf and at least one of Zr and Ce, and x is 0.2 to 0.4.

[0007] This thermal barrier coating material has low thermal conductivity, high coefficient of expansion and excellent resistance to sintering.

[0008] According to an embodiment of this application, the average particle size of the thermal barrier coating material is 30 μm to 110 μm.

[0009] According to embodiments of this application, the thermal barrier coating material satisfies at least one of the following conditions: the thermal conductivity of the thermal barrier coating material at 25°C to 600°C is 1.75 W / (m·K) to 3.0 W / (m·K); the average coefficient of thermal expansion of the thermal barrier coating material at 25°C to 1300°C is 10 × 10⁻⁶. -6 K -1 ~12×10 -6 K -1 The thermal barrier coating material has a density of 70%~85% and a fracture toughness of 2.0 MPa·m. 1 / 2 ~2.7 MPa·m 1 / 2 .

[0010] According to an embodiment of this application, the thermal barrier coating material has a fluorite phase structure.

[0011] A second aspect of this application provides a method for preparing the thermal barrier coating material, comprising: mixing a first oxide raw material with a second oxide raw material to obtain a mixture; and sintering the mixture to obtain the thermal barrier coating material.

[0012] The preparation method is simple in steps, easy to control parameters, has strong process adaptability, and the thermal barrier coating material has high batch stability, making it suitable for large-scale industrial production.

[0013] According to embodiments of this application, the first oxide raw material includes at least two of Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3 and Lu2O3; the second oxide raw material includes HfO2 and at least one of ZrO2 and CeO2.

[0014] According to an embodiment of this application, in the first oxide raw material, the molar amounts of each rare earth oxide are equal.

[0015] According to an embodiment of this application, the first oxide raw material is composed of a first sub-oxide raw material and a second sub-oxide raw material. The first sub-oxide raw material includes Sm2O3 and Gd2O3, and the second sub-oxide raw material includes at least one of Y2O3, Er2O3, Yb2O3 and Lu2O3.

[0016] According to an embodiment of this application, the molar ratio of the first sub-oxide raw material to the second sub-oxide raw material is 1:(1~1.2).

[0017] According to an embodiment of this application, the first oxide raw material is composed of three rare earth oxides, wherein the three rare earth oxides are any combination of three of Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3, and Lu2O3.

[0018] According to an embodiment of this application, the molar ratio of the three rare earth oxides is 1:(1~1.2):(1~1.2).

[0019] According to an embodiment of this application, the first oxide raw material is composed of four rare earth oxides, wherein the four rare earth oxides are any combination of four of Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3, and Lu2O3.

[0020] According to an embodiment of this application, the molar ratio of the four rare earth oxides is 1:1:(0.9-1.1):(0.9-1.1).

[0021] According to an embodiment of this application, the first oxide raw material is composed of five rare earth oxides, wherein the five rare earth oxides are any five combinations selected from Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3, and Lu2O3.

[0022] According to an embodiment of this application, the molar ratio of the five rare earth oxides is 1:1:(0.9-1.1):(0.9-1.1):1.

[0023] According to an embodiment of this application, the molar ratio of the first oxide raw material to the second oxide raw material is 1:4 to 9:11.

[0024] According to embodiments of this application, prior to the sintering process, the mixture is further subjected to spray granulation and / or pre-compression molding.

[0025] According to embodiments of this application, the average particle size of the first oxide and the second oxide is 0.2 μm to 3 μm.

[0026] A third aspect of this application provides a thermal barrier coating, comprising the thermal barrier coating material described above, or a thermal barrier coating material prepared using the method described above. This thermal barrier coating exhibits low thermal conductivity, excellent resistance to sintering, and long thermal cycling life, making it suitable for high-temperature service requirements.

[0027] According to an embodiment of this application, the thickness of the thermal barrier coating is 40 μm to 400 μm.

[0028] A fourth aspect of this application provides a method for preparing the aforementioned thermal barrier coating, comprising: subjecting a thermal barrier coating material to plasma spraying and / or electron beam physical vapor deposition to obtain the thermal barrier coating. This preparation method has simple procedures, good equipment compatibility, and is suitable for large-scale production.

[0029] A fifth aspect of this application provides a hot-end structural component comprising the thermal barrier coating described above, or a thermal barrier coating prepared using the method described above. This hot-end structural component possesses all the advantages of the thermal barrier coating described above, or all the advantages of the thermal barrier coating obtained by the method described above, which will not be elaborated further here.

[0030] The thermal barrier coating material of this application has at least the following beneficial effects: (1) Low thermal conductivity: Low thermal conductivity can significantly reduce the heat transfer from high-temperature gas to the internal structural component matrix, providing better heat insulation protection for hot-end structural components, effectively reducing the amount of cooling gas used, and improving the overall thermal efficiency and thrust-to-weight ratio of power equipment.

[0031] (2) High coefficient of thermal expansion: The high coefficient of thermal expansion greatly improves the thermal expansion matching between the thermal barrier coating and the substrate of the internal structural components, significantly alleviates the concentration of interfacial thermal stress during thermal cycling, reduces the risk of thermal barrier coating peeling failure, and extends the service life of the components.

[0032] (3) Excellent anti-sintering ability: Excellent anti-sintering ability ensures the long-term structural stability of the thermal barrier coating under extreme working conditions above 1300℃, and ensures that the thermal barrier coating maintains stable protective ability throughout its entire life cycle. Attached Figure Description

[0033] Figure 1 The X-ray diffraction patterns of the thermal barrier coating materials in Examples 1-4 of this application are shown below. Detailed Implementation The embodiments described below are exemplary and intended to explain the present application, and should not be construed as limiting the present application.

[0034] A first aspect of this application provides a thermal barrier coating material, the chemical formula of which is: Re x M (1-x) O (2-x / 2) In the formula: Re includes at least two of Sm, Gd, Dy, Y, Er, Yb, and Lu; M includes Hf, and at least one of Zr and Ce; and x is 0.2 to 0.4. This thermal barrier coating material has low thermal conductivity, high coefficient of thermal expansion, and excellent resistance to sintering.

[0035] According to an embodiment of this application, the general chemical formula of the thermal barrier coating material is: Re x M (1-x) O (2-x / 2)In the formula, x is 0.2~0.4, and x can specifically be 0.2, 0.25, 0.3, 0.35, 0.4 or any two of them. Within the above range, sufficient oxygen vacancies and multi-scale lattice distortion can be introduced into the fluorite phase lattice, maximizing the entropy stabilization effect of multi-rare earth configurations, taking into account both low thermal conductivity and high-temperature phase stability, while ensuring the thermal expansion matching between the thermal barrier coating material and the high-temperature alloy substrate, and achieving synergistic optimization of thermal insulation capability and long service life under ultra-high temperature conditions.

[0036] According to an embodiment of this application, the thermal barrier coating material has a fluorite phase structure. The pure fluorite phase structure, relying on its open crystal framework, can significantly improve phonon scattering efficiency. While ensuring the high-temperature phase stability of the thermal barrier coating material, it simultaneously achieves synergistic optimization of high thermal expansion coefficient and low thermal conductivity, adapting to the long-life service requirements of high-temperature hot-end components.

[0037] This compositional design achieves multi-element disordered occupancy in the fluorite phase matrix lattice composed of Hf / Zr / Ce through the co-doping of various large-ionic-radius rare-earth elements. On the one hand, it introduces a large number of lattice distortions of different scales, which greatly enhances the point defect scattering, grain boundary scattering and oxygen vacancy scattering effects of phonons, thus cutting off the long-range heat transfer path of phonons at the intrinsic level. On the other hand, relying on the high configurational entropy stabilization effect brought about by the co-doping of multiple rare-earth elements, it greatly improves the Gibbs free energy stability of the system, so that the crystal structure of the thermal barrier coating material is always maintained in the optimal stability range of the fluorite phase.

[0038] Only when Re (i.e., at least two of Sm, Gd, Dy, Y, Er, Yb, and Lu) and M (i.e., Hf, and at least one of Zr and Ce) coexist can a thermodynamically stable high configurational entropy defect fluorite phase solid solution be formed. The co-doping of Re with multiple rare earth elements significantly widens the stable temperature range of the fluorite phase through the configurational entropy effect. Simultaneously, multi-scale lattice distortion and oxygen vacancies compress the phonon mean free path to the atomic scale, reducing thermal conductivity. Meanwhile, the stable crystal framework of M provides sufficient lattice capacity for the solid solution of Re, ensuring that the thermal expansion coefficient of the thermal barrier coating material matches that of the high-temperature alloy matrix, while simultaneously suppressing long-range migration of oxygen ions. The synergistic effect of these two elements achieves a simultaneous breakthrough in low thermal conductivity, high phase stability, and high thermal expansion matching.

[0039] In this application, the M component must contain Hf. Hf plays a role in stabilizing the structure at high temperatures. The bond energy of the Hf-O bond is significantly higher than that of the Zr-O and Ce-O bonds. 4+ With Zr 4+With nearly identical ionic radii, Hf can dissolve into cation sites without compromising the lattice stability of the fluorite phase, significantly enhancing the overall lattice bonding strength and increasing the activation energy for grain boundary diffusion and oxygen vacancy migration. This not only inhibits abnormal high-temperature grain growth and improves anti-sintering performance but also slows down the excessively rapid growth of thermally grown oxide layers. Furthermore, Hf can enhance phonon scattering. With a much larger atomic mass than Zr and Ce, Hf can introduce additional mass scattering centers, further cutting off long-range phonon heat transfer paths on top of the existing rare-earth doped lattice distortion scattering, effectively overcoming the service performance bottleneck of existing thermal barrier coatings.

[0040] According to the embodiments of this application, the average particle size of the thermal barrier coating material is 30μm to 110μm, specifically 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm or any two of them. Within the above range, it can fully adapt to the feed particle size requirements of mainstream thermal barrier coating deposition processes such as atmospheric plasma spraying and EB-PVD, ensuring that the porosity distribution of the deposited thermal barrier coating is uniform, and significantly improving the interfacial bonding strength and thermal cycling service stability between the thermal barrier coating and the high-temperature alloy substrate.

[0041] The average particle size of the thermal barrier coating material was tested according to GB / T 19077-2016.

[0042] According to an embodiment of this application, the thermal barrier coating material has a thermal conductivity of 1.75 W / (m·K) to 3.0 W / (m·K) at 25℃ to 600℃. Specifically, it can be 1.75 W / (m·K), 2 W / (m·K), 2.5 W / (m·K), 3.0 W / (m·K), or any two of them. Within the above range, it can build an efficient thermal barrier between the alloy matrix and the high-temperature combustion gas, significantly reducing the operating temperature of the hot-end components. At the same time, with high expansion matching, it reduces interfacial thermal stress, effectively improving the thermal efficiency and service life of the equipment.

[0043] The thermal conductivity of thermal barrier coating materials was tested according to GB / T 22588-2008.

[0044] According to the embodiments of this application, the test temperature for the thermal conductivity of the thermal barrier coating material is 25℃~600℃, specifically 25℃, 50℃, 100℃, 200℃, 300℃, 400℃, 500℃, 600℃ or any two of them. This temperature range can cover the actual operating temperature range of the thermal barrier coating material near the alloy substrate, accurately characterize the thermal insulation capability and interfacial thermal matching characteristics of the thermal barrier coating material in the low temperature range, and ensure the service reliability of the thermal barrier coating material under the full temperature gradient.

[0045] According to embodiments of this application, the thermal barrier coating material has an average coefficient of thermal expansion of 10 × 10⁻⁶ at temperatures ranging from 25°C to 1300°C. -6 K -1 ~12×10 -6 K -1 Specifically, it can be 10×10 -6 K -1 11×10 -6 K -1 12×10 -6 K -1 or any range thereof, the aforementioned range enables the thermal barrier coating material to achieve a high degree of thermal expansion matching with the high-temperature alloy substrate, significantly reduces interfacial thermal stress during thermal cycling, effectively inhibits cracking and spalling of the thermal barrier coating material, and significantly improves the long-life service reliability of hot-end components.

[0046] The average coefficient of thermal expansion of the thermal barrier coating material was tested according to GB / T 4339-2008.

[0047] According to the embodiments of this application, the test temperature for the average thermal expansion coefficient of the thermal barrier coating material is 25℃~1300℃, specifically 25℃, 50℃, 100℃, 200℃, 500℃, 1000℃, 1100℃, 1200℃, 1300℃ or any two of them. The above temperature range can completely cover the entire temperature span of the thermal barrier coating material from room temperature to ultra-high temperature service, and can accurately characterize the thermal expansion matching characteristics of the thermal barrier coating material and the high-temperature alloy substrate under all working conditions, providing reliable data support for interface thermal stress assessment and thermal cycle life prediction.

[0048] According to the embodiments of this application, the density of the thermal barrier coating material is 70%~85%, specifically it can be 70%, 75%, 80%, 85% or any two of them. Within the above range, it can ensure that the powder particles of the thermal barrier coating material have sufficient sintering neck connection strength, and can also retain an appropriate amount of porosity to reserve space for particle collision deformation, effectively buffering thermal cycle stress.

[0049] The density of thermal barrier coating materials was tested according to GB / T 25995-2010.

[0050] According to an embodiment of this application, the fracture toughness of the thermal barrier coating material is 2.0 MPa·m. 1 / 2 ~2.7 MPa·m 1 / 2 Specifically, it could be 2.0 MPa·m 1 / 2 2.2 MPa·m 1 / 2 2.4 MPa·m 1 / 2 2.6 MPa·m 1 / 2 2.7 MPa·m1 / 2 or any two of the above ranges, within which the thermal barrier coating material can effectively improve its ability to resist crack propagation, suppress the rapid propagation of vertical cracks and interlayer cracks during thermal cycling, and significantly enhance the service reliability and service life of the thermal barrier coating material under ultra-high temperature thermal shock conditions.

[0051] The fracture toughness of thermal barrier coating materials was tested according to GB / T 23806-2025.

[0052] A second aspect of this application provides a method for preparing the thermal barrier coating material, comprising: S10. Mix the first oxide raw material with the second oxide raw material to obtain a mixture. This step ensures that the rare earth elements are uniformly distributed in the system, providing a foundation for the subsequent formation of a highly uniform pure fluorite phase structure.

[0053] According to embodiments of this application, the first oxide raw material is selected from oxides or hydroxides containing at least two rare earth elements selected from Sm, Gd, Dy, Y, Er, Yb, and Lu. Examples include Sm₂O₃, Sm(OH)₃, Gd₂O₃, and Gd(OH)₃. The range of selectable first oxide raw materials is expanded to include both oxides and hydroxides of specified rare earth elements, significantly broadening the process window for raw material procurement and preparation. This ensures uniform doping of rare earth elements during subsequent solid-state reactions, simultaneously achieving stable performance and reduced preparation costs for the thermal barrier coating material.

[0054] According to embodiments of this application, the second oxide raw material is selected from oxides or hydroxides of rare earth element Hf, and at least one of Zr and Ce. For example, it can be HfO2, Hf(OH)4, etc. By expanding the range of selectable second oxide raw materials to oxides, hydroxides and any mixtures of Hf, Zr and Ce, the raw material selection space for thermal barrier coating materials can be greatly broadened, without strictly limiting the precursor morphology, effectively reducing the raw material procurement threshold and preparation cost at the mass production stage.

[0055] According to embodiments of this application, the first oxide raw material includes at least two of Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3, and Lu2O3. Selecting the above raw materials can enhance the lattice distortion effect by utilizing the radius and atomic weight differences of different rare earth ions, significantly increase the configuration entropy of the thermal barrier coating material, stably maintain the fluorite phase structure of the thermal barrier coating material, and simultaneously achieve synergistic optimization of reduced thermal conductivity, increased thermal expansion coefficient, and enhanced anti-sintering performance.

[0056] Sm₂O₃, a light rare earth oxide with a large atomic mass, can enhance phonon scattering and reduce thermal conductivity in thermal barrier coatings by increasing the atomic mass difference. Gd₂O₃, a medium-heavy rare earth oxide, is a classic phase stabilizer and thermal expansion regulator in thermal barrier coatings, effectively maintaining the stability of the fluorite phase structure and improving the coating's thermal expansion coefficient. Dy₂O₃, also a medium-heavy rare earth oxide with a high atomic mass and moderate ionic radius, can further enhance lattice distortion in thermal barrier coatings, synergistically improving thermal insulation performance and anti-sintering ability. Yb₂O₃, a classic stabilizer in thermal barrier coatings, can effectively suppress the high thermal conductivity of zirconium oxide. The phase transition maintains the long-term stability of the cubic fluorite phase structure; Er2O3, a medium-heavy rare earth oxide, can increase interfacial scattering in thermal barrier coatings through moderate ion size mismatch, while improving the high-temperature toughness and thermal shock resistance of the thermal barrier coating; Yb2O3, a heavy rare earth oxide with high atomic weight and small ionic radius, can significantly enhance the phonon scattering effect in thermal barrier coatings, greatly reducing the high-temperature thermal conductivity of the material; Lu2O3, one of the rare earth oxides with the largest atomic weight, can achieve an extreme reduction in thermal conductivity in thermal barrier coatings through a very strong mass fluctuation scattering mechanism, while improving the high-temperature anti-sintering performance of the thermal barrier coating.

[0057] According to an embodiment of this application, the second oxide includes HfO2, and at least one of ZrO2 and CeO2. Selecting the above materials can rely on their intrinsic properties of high melting point and high coefficient of thermal expansion to stably maintain the fluorite phase skeleton structure and improve the high-temperature resistance to sintering and hot corrosion of the thermal barrier coating material.

[0058] HfO2 is a high-melting-point, high-hardness, high-performance ceramic material. In thermal barrier coatings, its excellent high-temperature chemical stability and high dielectric properties can enhance the high-temperature corrosion resistance and structural durability of the coatings. ZrO2 is the core matrix material of thermal barrier coatings. After being stabilized by rare earth doping, it can form a classic fluorite phase structure. Relying on its low thermal conductivity and high coefficient of thermal expansion, it provides basic thermal insulation protection and thermophysical properties that are compatible with the alloy matrix. CeO2 is a commonly used phase-modulating component in thermal barrier coatings. By inducing moderate lattice distortion through doping, it can reduce the elastic modulus of the material, improve the thermal shock resistance of the thermal barrier coating, optimize high-temperature phase stability, and extend the service life of thermal cycling.

[0059] According to an embodiment of this application, in the first oxide, the molar amounts of each rare earth oxide are equal. By limiting the molar amounts of each rare earth oxide in the first oxide to be equal, the configurational entropy gain effect of multiple rare earth elements can be maximized, achieving a uniform distribution of lattice distortion and simultaneously enhancing phonon scattering efficiency. While stabilizing the pure fluorite phase structure, this further synergistically improves the low thermal conductivity and anti-sintering performance of the thermal barrier coating material.

[0060] According to the embodiments of this application, in the first oxide raw material, the molar amounts of each rare earth oxide are equal, which can achieve complete disordered occupancy of multiple rare earth ions in the fluorite phase lattice, maximize the configuration entropy stabilization effect, and form the most uniform multi-scale lattice distortion distribution, achieve optimal coverage of phonon scattering across the entire frequency band, maximize the reduction of thermal conductivity of the thermal barrier coating material, and ensure the high-temperature stability of the phase structure.

[0061] According to embodiments of this application, the first oxide raw material is composed of a first sub-oxide raw material and a second sub-oxide raw material. The first sub-oxide raw material includes Sm2O3 and Gd2O3, and the second sub-oxide raw material includes at least one of Y2O3, Er2O3, Yb2O3, and Lu2O3. Selecting the above material combination can ensure configurational entropy gain, regulate the degree of lattice distortion, stably maintain the fluorite phase structure, and simultaneously achieve synergistic optimization of reduced thermal conductivity, increased coefficient of thermal expansion, and anti-sintering performance.

[0062] According to an embodiment of this application, the molar ratio of the first sub-oxide raw material to the second sub-oxide raw material is 1:(1~1.2), specifically it can be 1:1, 1:1.1, 1:1.2 or any two of them. Within the above range, the lattice distortion and phonon scattering effect can be optimally matched, and while stabilizing the fluorite phase structure, the low thermal conductivity and high temperature anti-sintering performance of the thermal barrier coating material can be further synergistically improved.

[0063] According to an embodiment of this application, the first oxide raw material is composed of three rare earth oxides, wherein the three rare earth oxides are any combination of three selected from Sm₂O₃, Gd₂O₃, Dy₂O₃, Y₂O₃, Er₂O₃, Yb₂O₃, and Lu₂O₃. This raw material combination can controllably regulate lattice distortion and configurational entropy gain, stably obtaining a fluorite phase structure, and simultaneously achieving synergistic optimization of thermal conductivity, coefficient of thermal expansion, and anti-sintering performance.

[0064] According to the embodiments of this application, the molar ratio of the three rare earth oxides is 1:(1~1.2):(1~1.2), specifically it can be 1:1:1, 1:1.1:1.1, 1:1.2:1.2 or any two of them. Within the above range, the lattice distortion and phonon scattering effect can be evenly distributed, which can further improve the low thermal conductivity and high temperature anti-sintering performance of the thermal barrier coating material while stabilizing the fluorite phase structure.

[0065] According to an embodiment of this application, the first oxide raw material is composed of four rare earth oxides, wherein the four rare earth oxides are any combination of four selected from Sm₂O₃, Gd₂O₃, Dy₂O₃, Y₂O₃, Er₂O₃, Yb₂O₃, and Lu₂O₃. This raw material can further enhance the configuration entropy level, strengthen the lattice distortion effect induced by multi-ion synergy, stably maintain the pure fluorite phase structure, and simultaneously achieve better synergy in thermal conductivity, coefficient of thermal expansion, and anti-sintering performance.

[0066] According to the embodiments of this application, the molar ratio of the four rare earth oxides is 1:1:(0.9~1.1):(0.9~1.1), specifically 1:1:0.9:0.9, 1:1:1:1, 1:1:1.1:0.9, 1:1:1.1:1.1, or any two of these ranges. Within the above range, lattice distortion and phonon scattering effects can be uniformly distributed, stabilizing the fluorite phase structure while further synergistically improving the low thermal conductivity and high-temperature sintering resistance of the thermal barrier coating material.

[0067] According to embodiments of this application, the first oxide raw material is composed of five rare earth oxides, wherein the five rare earth oxides are any five combinations selected from Sm₂O₃, Gd₂O₃, Dy₂O₃, Y₂O₃, Er₂O₃, Yb₂O₃, and Lu₂O₃. The above material can further improve the configuration entropy level, enhance the lattice distortion effect induced by multi-ion synergy, stably maintain the pure fluorite phase structure, and simultaneously achieve better synergy in thermal conductivity, coefficient of thermal expansion, and anti-sintering performance.

[0068] According to the embodiments of this application, the molar ratio of the five rare earth oxides is 1:1:(0.9~1.1):(0.9~1.1):1, specifically it can be 1:1:0.9:0.9:1, 1:1:1:1:1, 1:1:1.1:0.9:1, 1:1:1.1:1.1:1, or any two of them. Within the above range, the lattice distortion and phonon scattering effect can be uniformly distributed, which can further synergistically improve the low thermal conductivity and high temperature anti-sintering performance of the thermal barrier coating material while stabilizing the fluorite phase structure.

[0069] According to the embodiments of this application, the molar ratio of the first oxide raw material to the second oxide raw material is 1:4 to 9:11, specifically 1:4, 3:7, 2:3, 9:11 or any two of them. Within the above range, while ensuring the configuration entropy gain and lattice distortion effect brought about by rare earth doping, the system structure stability can be maintained by relying on the fluorite phase framework of the second oxide, thereby achieving synergistic optimization of low thermal conductivity and high temperature phase stability.

[0070] According to the embodiments of this application, the average particle size of the first oxide raw material and the second oxide raw material is 0.2 μm to 3 μm, specifically 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any two of them. Within the above range, the ion diffusion distance of the high-temperature solid-phase reaction can be significantly shortened, promoting the uniform formation of the fluorite phase solid solution, while ensuring the uniformity of multi-component mixing.

[0071] The average particle size of the first oxide raw material and the second oxide raw material was tested according to GB / T 19077-2016.

[0072] According to an embodiment of this application, the mixing is carried out under ball milling dispersion conditions. The ball milling dispersion method includes at least one of wet planetary ball milling, dry drum ball milling, and stirred ball milling. This step does not impose special limitations on the stirring operation method and process parameters, as long as the first oxide raw material and the second oxide raw material can be fully and uniformly dispersed. The specific ball-to-material ratio, rotation speed, and time parameters can be flexibly selected and adapted according to the actual amount of raw material powder to be processed.

[0073] S20. The mixture is sintered to obtain a thermal barrier coating material. This sintering process allows the rare earth components in the mixture to undergo a full solid-phase reaction with the second oxide, promoting the complete formation of a high configurational entropy pure fluorite phase structure, ensuring the component uniformity and phase structure stability of the final thermal barrier coating material, and simultaneously achieving the synergistic effect of low thermal conductivity, high coefficient of thermal expansion, and excellent anti-sintering performance.

[0074] According to an embodiment of this application, the sintering temperature is 1100℃~1600℃, specifically 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃ or any two of them. Within the above range, a fluorite phase thermal barrier coating material with high phase purity and uniform grain size can be obtained.

[0075] According to an embodiment of this application, the sintering time is 5h to 10h, specifically 5h, 6h, 7h, 8h, 9h, 10h or any two of them. Within the above range, a fluorite phase thermal barrier coating material with high phase purity and uniform grain size can be obtained.

[0076] According to embodiments of this application, prior to the sintering process, the mixture is further subjected to spray granulation and / or pre-compression molding. Spray granulation and / or pre-compression molding of the mixture before sintering can significantly improve the density and particle uniformity of the mixture, reducing problems such as component segregation and incomplete local reactions during subsequent high-temperature solid-phase reactions, and ensuring the phase structure purity and batch performance consistency of the final thermal barrier coating material.

[0077] Spray granulation is a process in which a mixture of materials and binders is formulated into a uniform suspension, which is then atomized into micron-sized droplets at high speed by an atomizer. The droplets are then rapidly dehydrated and solidified in a hot air drying tower to obtain spherical agglomerated powder. When used in the preparation of thermal barrier coating materials, it can significantly improve the flowability and bulk density of the powder.

[0078] According to the embodiments of this application, the spray granulation method includes at least one of centrifugal atomization spray granulation, pressure atomization spray granulation, and airflow atomization spray granulation. This step does not impose special limitations on the operation method and process parameters of spray granulation, as long as uniform atomization and rapid drying of the mixed suspension can be achieved. The specific binder selection, binder solution concentration, inlet air temperature, atomization speed, and feed rate parameters can be flexibly selected and adapted according to the actual amount of raw material powder to obtain agglomerated powder with high sphericity and good flowability, which facilitates the stable implementation of subsequent high-temperature sintering and thermal barrier coating spraying processes.

[0079] According to the embodiments of this application, when sintering is performed after spray granulation, the sintering temperature is 1350℃~1500℃, specifically 1350℃, 1400℃, 1450℃, 1500℃ or any two of them. The above temperature range can rely on the high density characteristics of the granulated powder to ensure that the multi-rare earth components fully complete the solid-phase reaction and form a pure fluorite phase structure.

[0080] Pre-compression molding is a powder pretreatment process in which a mixed powder is placed in a rigid mold and pressed into a pre-defined shape under constant pressure. When used in the preparation of thermal barrier coating materials, it can significantly improve the powder packing density, reduce the diffusion distance between particles, lower the activation energy of subsequent high-temperature solid-phase reactions, and ensure the uniformity of the phase structure and the stability of the final thermal barrier coating material. Pre-compression molding can form a material preform, facilitating subsequent molding and synthesis on devices.

[0081] According to the embodiments of this application, the pre-pressing method includes at least one of cold steel mold unidirectional pressing and cold isostatic pressing. This step does not impose special limitations on the operation method and process parameters of pre-pressing, as long as the uniform and dense packing of the mixed powder can be achieved without obvious delamination and cracking defects. The specific pressing pressure and holding time parameters can be flexibly selected and adapted according to the actual amount of raw material powder to obtain a uniformly dense thermal barrier coating material blank, which facilitates the full progress of the subsequent high-temperature solid-state sintering reaction.

[0082] According to the embodiments of this application, when sintering is performed after pre-pressing, the sintering temperature is 1400℃~1600℃, specifically 1400℃, 1450℃, 1500℃, 1550℃, 1600℃ or any two of them. The above temperature range can rely on the high density characteristics of the granulated powder to ensure that the multi-rare earth components fully complete the solid-phase reaction and form a pure fluorite phase structure.

[0083] A third aspect of this application provides a thermal barrier coating, comprising the thermal barrier coating material described above, or a thermal barrier coating material prepared using the method described above. This thermal barrier coating exhibits low thermal conductivity, excellent resistance to sintering, and long thermal cycling life, making it suitable for high-temperature service requirements.

[0084] The thermal barrier coating provided in this application is a ceramic protective layer deposited on the surface of hot-end components of high-temperature alloys. Using the thermal barrier coating material prepared in this scheme as the core raw material, and relying on the strong lattice distortion and phonon scattering effect induced by high configuration entropy, it achieves synergistic optimization of low thermal conductivity, high thermal expansion matching and excellent anti-sintering performance. It can form a stable thermal barrier on the surface of components such as turbine blades of aero-engines and high-temperature heated parts of heavy-duty gas turbines, significantly reducing the service temperature of the substrate, reducing high-temperature oxidation and hot corrosion damage, and effectively extending the service life of core hot-end components while improving the thermal efficiency and thrust-to-weight ratio of the equipment.

[0085] According to the embodiments of this application, the thickness of the thermal barrier coating is 40 μm to 400 μm, specifically it can be 40 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm or any two of them. Within the above range, the thermal barrier coating can ensure the long-term thermal cycling stability of the thermal barrier coating under operating conditions above 1300℃, while ensuring that the thermal barrier coating provides sufficient thermal insulation to the hot end component substrate.

[0086] The ultra-high temperature in this application refers to the long-term service conditions of thermal barrier coatings or thermal barrier coating materials within the temperature range of 1300℃ to 1700℃, corresponding to the extreme working environment of hot-end components of next-generation aero-engines and heavy-duty gas turbines. This temperature range is completely different from the conventional upper limit of 1200℃ for traditional YSZ thermal barrier coatings. Relying on the intrinsic high-temperature stability of the high configurational entropy pure fluorite phase, it can maintain low thermal conductivity, high thermal expansion matching and excellent anti-sintering performance for a long time within this temperature range, meeting the extreme operating condition protection requirements of hot-end components of next-generation aero-engines and heavy-duty gas turbines.

[0087] A fourth aspect of this application provides a method for preparing the aforementioned thermal barrier coating, comprising: subjecting a thermal barrier coating material to plasma spraying and / or electron beam physical vapor deposition to obtain the thermal barrier coating. This preparation method has simple procedures, good equipment compatibility, and is suitable for large-scale production.

[0088] The plasma spraying and / or electron beam physical vapor deposition used in this application for depositing thermal barrier coatings are both recognized conventional and mature mainstream processes in the field of thermal barrier coating preparation. They have been widely used in the preparation of protective coatings for hot-end components of high-end equipment such as aero-engines and heavy-duty gas turbines. Their equipment structure, operation process and process parameter selection are all common knowledge in the field of those skilled in the art and do not require special limitations. Those skilled in the art can flexibly select the appropriate process type and parameter combination according to the structural dimensions, service conditions and coating performance requirements of the workpiece to be protected, so as to stably obtain thermal barrier coatings with qualified bonding strength and uniform structure.

[0089] According to embodiments of this application, plasma spraying can melt or partially melt particulate thermal barrier coating material and apply it to the device requiring a thermal barrier coating to form a thermal barrier coating. This process can fully utilize the high enthalpy and high particle kinetic energy characteristics of the technology to ensure the interfacial bonding strength between the thermal barrier coating and the hot-end component substrate, and quickly form a layered, uniform, and dense thermal barrier coating structure, which is suitable for the large-scale mass production needs of aero-engine blades and gas turbine hot-end components.

[0090] According to the embodiments of this application, the plasma spraying includes at least one of atmospheric plasma spraying, low-pressure plasma spraying, and supersonic plasma spraying. This step does not impose special limitations on the operation mode and process parameters of plasma spraying, as long as it can achieve high adhesion and low defect deposition of the thermal barrier coating on the surface of the high-temperature alloy hot end component. The specific spraying power, powder feeding rate, and spraying distance parameters can be flexibly selected and adapted according to the structural size of the workpiece to be processed and the actual service conditions, so as to obtain a thermal barrier coating with uniform porosity distribution and dense interlayer bonding.

[0091] Electron beam physical vapor deposition (EB-PVD) is a thin film preparation technology that uses a high-energy electron beam to bombard a target material in a water-cooled crucible under high vacuum conditions, causing it to vaporize instantaneously. The gaseous atoms are then directionally deposited on the substrate surface under the guidance of a deflection magnetic field. When used in the preparation of the thermal barrier coating in this application, it can form a columnar crystal structure with consistent orientation, which can significantly improve the strain tolerance and thermal shock resistance of the thermal barrier coating. The thermal barrier coating is connected to the high-temperature alloy substrate by a metallurgical bonding method, with high bonding strength, which is suitable for the long service life requirements of high-end hot-end components such as turbine blades of aero-engines.

[0092] According to the embodiments of this application, the electron beam physical vapor deposition includes at least one of single-source EB-PVD, multi-source co-evaporation EB-PVD, and ion beam assisted EB-PVD. This step does not impose special limitations on the operation mode and process parameters of electron beam physical vapor deposition, as long as it can achieve high adhesion and low defect deposition of thermal barrier coating on the surface of high-temperature alloy hot end components. The specific electron gun power, vacuum chamber background vacuum degree, and substrate preheating temperature parameters can be flexibly selected and adapted according to the structural size of the workpiece to be processed and the actual service conditions, so as to obtain a thermal barrier coating with consistent columnar crystal orientation and high interfacial metallurgical bonding strength, ensuring its long-term service stability under extreme thermal cycling conditions above 1300℃.

[0093] A fifth aspect of this application provides a hot-end structural component comprising the thermal barrier coating described above, or a thermal barrier coating prepared using the method described above. This hot-end structural component possesses all the advantages of the thermal barrier coating described above, or all the advantages of the thermal barrier coating obtained by the method described above, which will not be elaborated further here.

[0094] Hot-end structural components are core load-bearing parts in high-end power equipment such as aero engines and heavy-duty gas turbines, which are subjected to high-temperature gas scouring and complex thermal stress coupling conditions above 1000°C for a long time. Typical components include turbine blades, combustion chamber flame tubes, and afterburner regulating plates. With the thermal barrier coating of this application for surface protection, the structural integrity and long service life can be maintained while breaking through the upper limit of the traditional high-temperature alloy operating temperature. They are the core key components that determine the thermal efficiency, thrust-to-weight ratio and operational reliability of power equipment.

[0095] The following will explain the solution of this application with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0096] The technical solution of the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.

[0097] Example 1: Preparation (Sm 0.2 Gd 0.2 Dy 0.2 Er 0.2 Yb 0.2 ) 0.4 (Zr 0.95 Hf 0.05 ) 0.6 O1.8 Thermal barrier coating materials include: (1) The raw materials Sm2O3, Gd2O3, Dy2O3, Er2O3, Yb2O3, HfO2 and ZrO2 are calcined at 1100℃ for 2 hours to remove impurities such as water and carbon dioxide adsorbed in the raw materials, and dry first oxide raw materials and second oxide raw materials are obtained; wherein, the first oxide raw material includes Sm2O3, Gd2O3, Dy2O3, Er2O3 and Yb2O3, and the average particle size of the first oxide raw material is 2.5 μm; the second oxide raw material includes HfO2 and ZrO2, and the average particle size of the second oxide raw material is 2.5 μm.

[0098] (2) The dried Sm2O3, Gd2O3, Dy2O3, Er2O3, Yb2O3, HfO2 and ZrO2 are arranged according to (Sm 0.2 Gd 0.2 Dy 0.2 Er 0.2 Yb 0.2 ) 0.4 (Zr 0.95 Hf 0.05 ) 0.6 O 1.8 Weigh out the molar ratio; (3) The weighed raw material powder is ball-milled and mixed with a dispersion liquid. The ball milling medium is zirconia balls, the dispersion liquid is 75% (v / v) alcohol, the mass ratio of raw material powder to zirconia balls is 1:12, and the amount of alcohol is 0.8 times the mass of powder and zirconia balls. The ball milling is carried out at a speed of 220 rpm / min for 6 hours to obtain ball mill slurry. (4) The ball mill slurry is separated by a rotary evaporator to obtain a mixed block containing the first oxide raw material and the second oxide raw material; (5) Grind the mixed material block containing the first oxide raw material and the second oxide raw material with zirconium oxide balls at a mass ratio of 1:12 for 6 hours, then pass it through a 300-mesh sieve to obtain powder, and then calcine the powder at 1150℃ for 5 hours to obtain pre-calcined powder. (6) The preliminarily calcined powder was ball-milled with zirconia balls at a mass ratio of 1:12 for 8 hours. The powder was then passed through a 200-mesh sieve to obtain powder. The powder was then calcined at 1560℃ for 6 hours to obtain powdered (Sm) 0.2 Gd 0.2 Dy 0.2 Er 0.2 Yb 0.2 ) 0.4 (Zr 0.95 Hf 0.05 ) 0.6 O1.8 Thermal barrier coating material, with an average particle size of 70 μm.

[0099] (7) A thermal barrier coating was prepared by plasma spraying, and the thickness of the prepared thermal barrier coating was 300 μm.

[0100] Example 2: A type of (Gd) 0.25 Dy 0.25 Er 0.25 Yb 0.25 ) 0.4 (Zr 0.9 Hf 0.1 ) 0.6 O 1.8 The thermal barrier coating material in this embodiment is prepared using the same method as that in Example 1, except that: In step (1), the raw materials are a first oxide raw material (Gd2O3, Dy2O3, Er2O3, Yb2O3) and a second oxide raw material (HfO2, ZrO2). The average particle size of the first oxide raw material is 2.5 μm, and the average particle size of the second oxide raw material is 2.5 μm.

[0101] In step (2), the dried (Gd) 0.25 Dy 0.25 Er 0.25 Yb 0.25 ) 0.4 (Zr 0.9 Hf 0.1 ) 0.6 O 1.8 Weigh according to the molar ratio of each raw material; The average particle size of the thermal barrier coating material obtained in step (6) is 70 μm.

[0102] In step (7), a thermal barrier coating is prepared by plasma spraying, and the thickness of the prepared thermal barrier coating is 400 μm.

[0103] Example 3: A type of (Gd) 0.25 Dy 0.25 Er 0.25 Yb 0.25 ) 0.4 (Zr 0.8 Hf 0.1 Ce 0.1 ) 0.6 O 1.8 The thermal barrier coating material in this embodiment is prepared using the same method as that in Example 1, except that: In step (1), the raw materials are a first oxide raw material (Gd2O3, Dy2O3, Er2O3, Yb2O3) and a second oxide raw material (HfO2, ZrO2, CeO2). The average particle size of the first oxide raw material is 3 μm, and the average particle size of the second oxide raw material is 3 μm.

[0104] In step (2), the dried (Gd) 0.25 Dy 0.25 Er 0.25 Yb 0.25 ) 0.4 (Zr 0.9 Hf 0.1 Ce 0.1 ) 0.6 O 1.8 Weigh out the raw materials according to their molar ratios.

[0105] The average particle size of the thermal barrier coating material obtained in step (6) is 70 μm.

[0106] In step (7), a thermal barrier coating is prepared using electron beam physical vapor deposition, and the thickness of the prepared thermal barrier coating is 100 μm.

[0107] Example 4: A type of (Gd) 0.25 Dy 0.25 Y 0.25 Lu 0.25 ) 0.4 (Zr 0.9 Hf 0.1 ) 0.6 O 1.8 The thermal barrier coating material in this embodiment is prepared using the same method as that in Example 1, except that: In step (1), the raw materials are a first oxide raw material (Gd2O3, Dy2O3, Y2O3, Lu2O3) and a second oxide raw material (HfO2, ZrO2). The average particle size of the first oxide raw material is 2.5 μm, and the average particle size of the second oxide raw material is 2.5 μm.

[0108] In step (2), the dried (Gd) 0.25 Dy 0.25 Y 0.25 Lu 0.25 ) 0.4 (Zr 0.9 Hf 0.1 ) 0.6 O 1.8 Weigh out the raw materials according to their molar ratios.

[0109] The average particle size of the thermal barrier coating material obtained in step (6) is 70 μm.

[0110] In step (7), a thermal barrier coating is prepared by plasma spraying, and the thickness of the prepared thermal barrier coating is 400 μm.

[0111] Example 5: A type of (Gd) 0.5 Dy 0.5 ) 0.4 (Zr 0.9 Hf 0.1 ) 0.6 O 1.8 The thermal barrier coating material in this embodiment is prepared using the same method as that in Example 1, except that: In step (1), the raw materials are a first oxide raw material (Gd2O3, Dy2O3) and a second oxide raw material (HfO2, ZrO2). The average particle size of the first oxide raw material is 2.5 μm, and the average particle size of the second oxide raw material is 2.5 μm.

[0112] In step (2), the dried (Gd) 0.5 Dy 0.5 ) 0.4 (Zr 0.9 Hf 0.1 ) 0.6 O 1.8 Weigh out the raw materials according to their molar ratios.

[0113] The average particle size of the thermal barrier coating material obtained in step (6) is 70 μm.

[0114] In step (7), a thermal barrier coating is prepared by plasma spraying, and the thickness of the prepared thermal barrier coating is 400 μm.

[0115] Example 6 A type of (Gd) 0.34 Dy 0.33 Er 0.33 ) 0.3 (Zr 0.9 Hf 0.1 ) 0.7 O 1.85 The thermal barrier coating material in this embodiment is prepared using the same method as that in Example 1, except that: In step (1), the raw materials are the first oxide raw materials (Gd2O3, Dy2O3, Er2O3), the average particle size of the first oxide raw materials is 3 μm, and the average particle size of the second oxide raw materials is 3 μm.

[0116] In step (2), the dried (Gd) 0.34 Dy 0.33 Er 0.33 ) 0.3 (Zr 0.9 Hf 0.1 ) 0.7 O 1.85 Weigh out the raw materials according to their molar ratios.

[0117] The average particle size of the thermal barrier coating material obtained in step (6) is 70 μm.

[0118] In step (7), a thermal barrier coating is prepared by plasma spraying, and the thickness of the prepared thermal barrier coating is 400 μm.

[0119] Example 7 A type (Sm) 0.25 Gd 0.25 Er 0.5 ) 0.3 (Zr 0.9 Hf 0.1 ) 0.7 O 1.85 The thermal barrier coating material in this embodiment is prepared using a method that is basically the same as that in Example 1, except that: In step (1), the raw materials are first oxide raw materials (Sm2O3, Gd2O3, Er2O3), the average particle size of the first oxide raw materials is 2 μm, and the average particle size of the second oxide raw materials is 2 μm.

[0120] In step (2), the dried (Sm) 0.34 Gd 0.33 Er 0.33 ) 0.3 (Zr 0.9 Hf 0.1 ) 0.7 O 1.85 Weigh out the raw materials according to their molar ratios.

[0121] The average particle size of the thermal barrier coating material obtained in step (6) is 70 μm.

[0122] In step (7), a thermal barrier coating is prepared by plasma spraying, and the thickness of the prepared thermal barrier coating is 400 μm.

[0123] Example 8 A type (Sm) 0.2 Gd 0.2 Dy 0.2 Er 0.2 Yb 0.2 ) 0.2 (Zr0.9 Hf 0.1 ) 0.8 O 1.9 The thermal barrier coating material in this embodiment is prepared using a method that is basically the same as that in Example 1, except that: In step (1), the raw materials are a first oxide raw material (Sm2O3, Gd2O3, Dy2O3, Er2O3, Yb2O3) and a second oxide raw material (HfO2, ZrO2). The average particle size of the first oxide raw material is 2.0 μm, and the average particle size of the second oxide raw material is 2.5 μm.

[0124] In step (2), the dried (Sm) 0.2 Gd 0.2 Dy 0.2 Er 0.2 Yb 0.2 ) 0.2 (Zr 0.9 Hf 0.1 ) 0.8 O 1.9 Weigh out the raw materials according to their molar ratios.

[0125] The average particle size of the thermal barrier coating material obtained in step (6) is 70 μm.

[0126] In step (7), a thermal barrier coating is prepared by plasma spraying, and the thickness of the prepared thermal barrier coating is 400 μm.

[0127] Comparative Example 1 The preparation method according to Example 1 differs in that the raw material selected is commercial YSZ powder, purchased from Jiangsu Gaoke Special Materials Co., Ltd., and the powder composition is 4 mol% Y2O3 doped with ZrO2 with an average particle size of 80 μm. In step (7), a thermal barrier coating is prepared by plasma spraying, and the thickness of the prepared thermal barrier coating is 500 μm.

[0128] The performance test results of Examples 1-8 and Comparative Example 1 are shown in the table below.

[0129] Table 1 Performance Test Results

[0130] Test method: (1) Average thermal expansion coefficient: The thermal barrier coating material was sintered into a cylindrical standard sample with a length of 25 mm and a diameter of 6 mm. A push rod type thermal expansion coefficient tester was used, strictly following the ASTM E831-06 thermomechanical analysis test specification. The temperature was continuously increased from 25 °C to 1300 °C in a static air atmosphere at a uniform heating rate of 5 °C / min. The axial length change of the sample was collected in real time throughout the process. The average thermal expansion coefficient of the entire range from room temperature (25 °C) to 1300 °C was calculated by linear fitting. The push rod load was kept constant at 0.5 N during the test to avoid measurement error caused by probe indentation.

[0131] (2) Thermal conductivity: The thermal barrier coating material was sintered into a standard square thermal barrier coating material block sample of 10mm×10mm×1mm. A thin graphite light-absorbing layer was uniformly sprayed on the two parallel surfaces of the sample to eliminate laser transmission interference. The thermal diffusivity λ of the sample was obtained by testing with a laser flare instrument (LFA) under an argon protective atmosphere. The specific heat capacity Cp of the material at the corresponding temperature was calculated by Neumann-Kopp mixing law. Combined with the actual density ρ of the sample measured in advance by Archimedes' water displacement method, the thermal conductivity of the thermal barrier coating material at the corresponding temperature point was accurately calculated by the formula κ=ρ·Cp·λ.

[0132] (3) Density: The density of thermal barrier coating materials is tested according to ASTM B962-14.

[0133] (4) Fracture toughness: The fracture toughness of thermal barrier coating materials is tested according to ASTM C 1421-18.

[0134] Results analysis: (1) From Figure 1 It can be concluded that the X-ray diffraction (111) peak of the thermal barrier coating material in Example 1 is at 28.8°, the X-ray diffraction (111) peak of the multi-element rare earth thermal barrier coating material in Example 2 is at 28.6°, the X-ray diffraction (111) peak of the multi-element rare earth thermal barrier coating material in Example 3 is at 28.6°, and the X-ray diffraction (111) peak of the multi-element rare earth thermal barrier coating material in Example 4 is at 28.9°. Comparison with the X-ray diffraction peaks of the fluorite structure shows that the X-ray diffraction peaks of the thermal barrier coating materials prepared in Examples 1-4 of this application satisfy Fd... The m-space group is the standard space characteristic group for fluorite structures, indicating that the prepared thermal barrier coating material has a distinct fluorite structure.

[0135] (2) The average coefficient of thermal expansion of the thermal barrier coating materials in Examples 1-8 from room temperature (25°C) to 1300°C is 10.4 × 10⁻⁶. -6 K -1 ~11.2×10 -6 K-1 The coefficient of thermal expansion is less than that of Comparative Example 1. This indicates that the high configurational entropy fluorite phase solid solution constructed by co-doping with multiple rare earth elements in this application can further optimize the thermal expansion behavior of the thermal barrier coating material while achieving low thermal conductivity. This makes the interfacial thermal stress distribution between the thermal barrier coating and the high-temperature alloy substrate more uniform, which is beneficial to improving the long-life service reliability of the thermal barrier coating.

[0136] (3) The thermal barrier coating materials in Examples 1-8 have a thermal conductivity of 1.54 W / (m·K)~1.75 W / (m·K) at 600℃, which is lower than that of Comparative Example 1 (2.8 W / (m·K). This indicates that the high configurational entropy fluorite phase solid solution constructed by co-doping with multiple rare earth elements in this application can introduce abundant oxygen vacancies and multi-scale lattice distortion in the crystal lattice, significantly enhance the phonon scattering effect, effectively cut off the long-range heat transfer path of phonons, and significantly reduce the thermal conductivity of the thermal barrier coating material at low temperatures from an intrinsic level. The thermal insulation performance is superior to that of the existing mainstream YSZ thermal barrier coating materials.

[0137] (4) The density of the thermal barrier coating materials in Examples 1-8 is 71%~83%, which is lower than 95% of Comparative Example 1. This indicates that the high configurational entropy fluorite phase solid solution constructed by multi-rare earth co-doping in this application can form a richer and more uniformly distributed microporous structure while maintaining the structural integrity and mechanical properties of the thermal barrier coating. These uniform pores can further enhance phonon scattering, reduce thermal conductivity, and effectively buffer interfacial thermal stress during thermal cycling, inhibit crack propagation, so that the thermal barrier coating has both excellent thermal insulation performance and good thermal shock resistance.

[0138] (5) The fracture toughness of the thermal barrier coating materials in Examples 1-8 is 2.2 MPa·m. 1 / 2 ~2.7 MPa·m 1 / 2 Slightly lower than 3 MPa·m in Comparative Example 1 1 / 2 Because the uniformly distributed microporous structure in the thermal barrier coating material of this application enhances phonon scattering and reduces thermal conductivity, it also has a certain impact on the fracture toughness of the thermal barrier coating material; however, the toughness level still fully meets the service toughness requirements of ultra-high temperature thermal barrier coatings, achieving performance optimization by exchanging minimal toughness loss for a thermal conductivity reduction of more than 38%, and the overall thermal insulation service performance is significantly better than that of traditional YSZ coatings.

[0139] In summary, this application achieves a comprehensive improvement in the overall performance of thermal barrier coating materials by designing them as high configurational entropy fluorite phase solid solutions co-doped with at least two rare earth elements. The thermal conductivity at 600℃ is only 1.54 W / (m·K)~1.75 W / (m·K), a reduction of more than 38% compared to traditional YSZ coatings, resulting in significantly enhanced thermal insulation performance. Simultaneously, it possesses excellent high-temperature phase stability and a suitable coefficient of thermal expansion, while maintaining a fracture toughness of 2.2 MPa·m.1 / 2 ~2.7 MPa·m 1 / 2 The thermal barrier coating material of this application breaks through the technical bottleneck of traditional YSZ coatings having high thermal conductivity and insufficient upper limit of operating temperature, and is fully adapted to the long service life requirements of ultra-high temperature hot-end components of new generation aero engines and heavy gas turbines at 1300℃~1700℃.

[0140] In the description of this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0141] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0142] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A thermal barrier coating material, characterized in that, The general chemical formula of the thermal barrier coating material is: Re x M (1-x) O (2-x / 2) In the formula: Re includes at least two of Sm, Gd, Dy, Y, Er, Yb and Lu, M includes Hf and at least one of Zr and Ce, and x is 0.2 to 0.

4.

2. The thermal barrier coating material according to claim 1, characterized in that, At least one of the following conditions must be met: The average particle size of the thermal barrier coating material is 30 μm to 110 μm; The thermal barrier coating material has a fluorite phase structure.

3. The thermal barrier coating material according to claim 1, characterized in that, At least one of the following conditions must be met: The thermal barrier coating material has a thermal conductivity of 1.75 W / (m·K) to 3.0 W / (m·K) at 25℃ to 600℃. The thermal barrier coating material has an average coefficient of thermal expansion of 10 × 10⁻⁶ at temperatures ranging from 25℃ to 1300℃. -6 K -1 ~12×10 -6 K -1 ; The density of the thermal barrier coating material is 70%~85%; The fracture toughness of the thermal barrier coating material is 2.0 MPa·m. 1 / 2 ~2.7 MPa·m 1 / 2 .

4. A method for preparing the thermal barrier coating material according to any one of claims 1 to 3, characterized in that, include: The first oxide raw material and the second oxide raw material are mixed to obtain a mixture; The mixture is sintered to obtain a thermal barrier coating material.

5. The method according to claim 4, characterized in that, The first oxide raw material includes at least two of Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3 and Lu2O3; the second oxide raw material includes HfO2 and at least one of ZrO2 and CeO2.

6. The method according to claim 4, characterized in that, It also meets at least one of the following conditions: In the first oxide raw material, the molar amounts of each rare earth oxide are equal; The molar ratio of the first oxide raw material to the second oxide raw material is 1:4 to 9:11; The average particle size of the first oxide raw material and the second oxide raw material is independently 0.2 μm to 3 μm.

7. The method according to claim 4, characterized in that, The first oxide raw material is composed of a first sub-oxide raw material and a second sub-oxide raw material. The first sub-oxide raw material includes Sm2O3 and Gd2O3, and the second sub-oxide raw material includes at least one of Y2O3, Er2O3, Yb2O3 and Lu2O3. The molar ratio of the first sub-oxide raw material to the second sub-oxide raw material is 1:(1~1.2).

8. The method according to claim 4, characterized in that, The first oxide raw material is composed of three rare earth oxides, wherein the three rare earth oxides are any combination of three of Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3, and Lu2O3; The molar ratio of the three rare earth oxides is 1:(1~1.2):(1~1.2).

9. The method according to claim 4, characterized in that, The first oxide raw material is composed of four rare earth oxides, and the four rare earth oxides are any combination of four of the following: Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3, and Lu2O3. The molar ratio of the four rare earth oxides is 1:1:(0.9-1.1):(0.9-1.1).

10. The method according to claim 4, characterized in that, The first oxide raw material is composed of five rare earth oxides, wherein the five rare earth oxides are any five combinations selected from Sm2O3, Gd2O3, Dy2O3, Y2O3, Er2O3, Yb2O3, and Lu2O3; The molar ratio of the five rare earth oxides is 1:1:(0.9~1.1):(0.9~1.1):

1.

11. The method according to claim 4, characterized in that, Prior to the sintering process, the mixture is further subjected to spray granulation and / or pre-compression molding.

12. A thermal barrier coating, characterized in that, Includes the thermal barrier coating material according to any one of claims 1 to 3, or the thermal barrier coating material prepared by the method according to any one of claims 4 to 11.

13. The thermal barrier coating according to claim 12, characterized in that, The thickness of the thermal barrier coating is 40 μm to 400 μm.

14. A method for preparing the thermal barrier coating according to claim 12 or 13, characterized in that, include: Thermal barrier coatings are obtained by plasma spraying and / or electron beam physical vapor deposition of thermal barrier coating materials.

15. A hot-end structural component, characterized in that, This includes the thermal barrier coating as described in claim 12 or 13, or the thermal barrier coating prepared using the method described in claim 14.